Load flow, largest motor starting, short circuit & protection relay coordination in gas compressor station / Hazrul Izwan Hussein - Hazrul Izwan, Hussein (2018)
The demand for oil and gas increases every year due to the immense development the world is currently undergoing. Oil and gas operating companies need to come up with innovative and optimistic design for the facilities to extract and deliver the oil and gas from the earth’s crust, processing and delivering to the user. Thus, having a reliable and robust power system design for the compressor station is vital. The main objective of this research is to perform load flow, largest motor starting, short circuit studies and relay protection coordination for the compressor station. The studies are performed using ETAP Power Systems Software. Based on the load flow studies performed, all the equipment steady state loading and voltage deviation is within the acceptable range. The largest motor starting study is performed to investigate and to confirm should the direct on-line method is practical for starting the largest motor to the system transient performance. From the motor starting study performed, a direct online starting method is sufficient to start the largest motor and the voltage drop occurs within the standard range. The short circuit studies were able to specify the maximum short circuit current all the high voltage and low voltage equipment in the system are required to withstand during a fault prior to tripping by the protection system. The final studies is the relay discrimination studies that showing how the sequence of response by relays accordingly to the desired setting. The results of the studies performed will be useful for electrical consultants to design an optimized, reliable and robust electrical network on compressor station.